2019
DOI: 10.3389/fnins.2019.01207
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Associated PNPLA6 Mutations Maintain Partial Functions When Analyzed in Drosophila

Abstract: Mutations in patatin-like phospholipase domain-containing protein 6 (PNPLA6) have been linked with a number of inherited diseases with clinical symptoms that include spastic paraplegia, ataxia, and chorioretinal dystrophy. PNPLA6 is an evolutionary conserved protein whose ortholog in Drosophila is Swiss-Cheese (SWS). Both proteins are phospholipases hydrolyzing lysophosphatidylcholine (LPC) and phosphatidylcholine (PC). Consequently, loss of SWS/PNPLA6 in flies and mice increases both lipids and leads to locom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…In this study, we elucidate mitochondria alterations, ROS acceleration, induction of antioxidant-associated genes expression and LD gene/protein overrepresentation upon sws dysfunction. In addition, SWS is known to be a (lyso)phospholipase itself, acting in lipid metabolism [ 21 , 57 ]. Therefore, we decided to test whether LDs could accumulate in the fly brain in the case of the neuronal sws knockdown.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we elucidate mitochondria alterations, ROS acceleration, induction of antioxidant-associated genes expression and LD gene/protein overrepresentation upon sws dysfunction. In addition, SWS is known to be a (lyso)phospholipase itself, acting in lipid metabolism [ 21 , 57 ]. Therefore, we decided to test whether LDs could accumulate in the fly brain in the case of the neuronal sws knockdown.…”
Section: Resultsmentioning
confidence: 99%
“…Our finding that the catalytic domain of NTE associates with LD and alters LD structure and cellular TAG may point to a previously unrecognized role of LDs in NTE-associated disorders. Most disease-associated NTE mutations were found in the catalytic region and some of these mutations have been linked to decreased NTE activity and altered LPC levels [18,20,[41][42][43]. This suggests impaired enzyme activity as the major pathomechanism of NTE-associated disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Recent elegant experiments in Drosophila have shown that certain mutations in SWS, the fruit-fly orthologue of NTE, produce neurodegenerative disease and disruption of phospholipid homeostasis that can be rescued by expressing wild-type NTE in the flies (Sunderhaus et al, 2019b). However, expression of NTE that contained disease-causing mutations in either the catalytic domain or the CNB domains suppressed neurological deficits but did not restore lipid homeostasis.…”
Section: Cyclic Nucleotide Binding (Cnb) Homology Domainsmentioning
confidence: 99%
“…The human NTE mutants included some with mutations in the catalytic domain and others with mutations in the region containing CNB domains. The results were interpreted to indicate that CNB regions could modulate NTE catalytic activity and that the mutant forms of human NTE retained some degree of their biological function, suggesting that disruption of the catalytic function of SWS was not the only factor in disease pathogenesis (Sunderhaus et al, 2019b).…”
Section: Nte Disease-causing Mutations In Humansmentioning
confidence: 99%
See 1 more Smart Citation